Membrane assembly of aquaporin-4 autoantibodies regulates classical complement activation in neuromyelitis optica - John Soltys; Yiting Liu; Alanna Ritchie; Scott Wemlinger; Kristin Schaller; Hannah Schumann; Gregory P. Owens; Jeffrey L. Bennett (The Journal of Clinical Investigation, 2019)
Neuromyelitis optica (NMO) is an autoimmune CNS disorder mediated by pathogenic aquaporin-4 (AQP4) water channel autoantibodies (AQP4-IgG). Although AQP4-IgG–driven complement-dependent cytotoxicity (CDC) is critical for the formation of NMO lesions, the molecular mechanisms governing optimal classical pathway activation are unknown. We investigated the molecular determinants driving CDC in NMO using recombinant AQP4–specific autoantibodies (AQP4 rAbs) derived from affected patients. We identified a group of AQP4 rAbs targeting a distinct extracellular loop C epitope that demonstrated enhanced CDC on target cells. Targeted mutations of AQP4 rAb Fc domains that enhance or diminish C1q binding or antibody Fc-Fc interactions showed that optimal CDC was driven by the assembly of multimeric rAb platforms that increase multivalent C1q binding and facilitate C1q activation. A peptide that blocks antibody Fc-Fc interaction inhibited CDC induced by AQP4 rAbs and polyclonal NMO patient sera. Super-resolution microscopy revealed that AQP4 rAbs with enhanced CDC preferentially formed organized clusters on supramolecular AQP4 orthogonal arrays, linking epitope-dependent multimeric assembly with enhanced C1q binding and activation. The resulting model of AQP4-IgG CDC provides a framework for understanding classical complement activation in human autoantibody–mediated disorders and identifies a potential new therapeutic avenue for treating NMO.